Harmonização tributária no Mercosul e o federalismo fiscal brasileiro: a instituição do imposto sobre o valor agregado (IVA) na tributação sobre o consumo e serviços no bloco regional - Schmidt, Otto Frederico (2009)
The impact of globalization has influenced the national states and also determined their regional economic integration. The concepts that orientate nowadays regional economic integration are far from those which inspired the foundation of national sovereigns. It means that Law as an institution has been suffering so many profound transformations that it requires a revision of the basis on which international public Law, and more recently, the comunitary Law are founded. The present work intends to contribute to the discussion and the systematization of economic integration processes, especially the Mercosul. In this context is the problem of the brazilian fiscal federalism and its chalenges to the future of the regional agreement, particularly the permanence of the ICMS (Circulation Tax about Goods and Services), the resistance of some sectors of the brazilian society to increase the Tributary Reform and also the implantation of the IVA (Value-Added Tax). There is a general consensus that if federal IVA was adopted by Brazil it would provide great advances to the tributary harmonization in Mercosul, for the reason that many national legislations´ principles would be convergent. The progress of the economic integration depends on it. A bibliographic review of economic integration theories - the mainly example is taken from the European Union is followed here by a comparative study of the tributary systems of the countries that belong to Mercosul, especially the Brazilian Tributary System and its influences to the consolidation of the integrationist process. The fiscal harmonization will be a mark of this study.